Foundations and frontiers in computer, communication and electrical engineering : proceedings of 3rd International Conference on Foundations and Frontiers in Computer, Communication and Electrical Engineering (C2E2-2016), Mankundu, West Bengal, India, 15th-16th January, 2016 /: proceedings of 3rd International Conference on Foundations and Frontiers in Computer, Communication and Electrical Engineering (C2E2-2016), Mankundu, West Bengal, India, 15th-16th January, 2016. ([2016]) - Unknown
No abstract available